Integrins regulation of wound healing processes: insights for chronic skin wound therapeutics - Yu, Dong; Lu, Zhaoyu; Nie, Fengsong; Chong, Yang (Frontiers in Cellular and Infection Microbiology, 2024)
Integrins are heterodimers composed of non-covalently associated alpha and beta subunits that mediate the dynamic linkage between extracellular adhesion molecules and the intracellular actin cytoskeleton. Integrins are present in various tissues and organs and are involved in different physiological and pathological molecular responses in vivo. Wound healing is an important process in the recovery from traumatic diseases and consists of three overlapping phases: inflammation, proliferation, and remodeling. Integrin regulation acts throughout the wound healing process to promote wound healing. Prolonged inflammation may lead to failure of wound healing, such as wound chronicity. One of the main causes of chronic wound formation is bacterial colonization of the wound. In this review, we review the role of integrins in the regulation of wound healing processes such as angiogenesis and re-epithelialization, as well as the role of integrins in mediating bacterial infections during wound chronicity, and the challenges and prospects of integrins as therapeutic targets for infected wound healing.